Community Empowerment Model Based on Independence in Administration Alert Village Health Sector - Suparji Suparji; Heru Santoso Wahito Nugroho; Sunarto Sunarto (Humanistic Network for Science and Technology (HNST), 2018)
Introduction: The success of “Alert villages” (“alert village”) can be explained using an independence-based